ANALISIS KINERJA SIMPANG BERSINYAL TANAH AJI – KOTA MATARAM DENGAN SOFTWARE PTV VISSIM - MAHENDRA, MADE; HASYIM, HASYIM (Universitas Mahasaraswati K. Mataram, 2024)
The Tanah Aji signalized intersection is one of the crossroads in Mataram City that links Jalan Sriwijaya with Jalan Majapahit and Jalan Airlangga with Jalan Gajah Mada . The Department of Transportation (DISHUB) officially reactivated the Tanah Aji signalized intersection (APILL) on Wednesday, December 14 2022. The aim of this research is to determine the performance of the Tanah Aji signalized intersection in Mataram City in its existing condition and provide solutions to improve performance. the signalized intersection. Primary and secondary data collecting was part of the research methodology. Secondary data is in the form of location map data obtained from Google Earth, traffic light cycles, and video recordings of intersections from the Mataram City Transportation Department (DISHUB). Next, analytical modeling of existing conditions is carried out. The results obtained show that the existing conditions produce a level of service E. The solution by modeling the flyover on Jalan Majapahit and Jalan Sriwijaya produces a level of service C. Comparison of the performance of the Tanah Aji intersection, Mataram City in the existing condition and the flyover solution from the results of the Vissim software analysis, is the existing condition, it was found that the length of the vehicle queue was 92,077 m Jl. Srivijaya; 231,275 m Jl. Gajah Mada; 177,973 m Jl. Majapahit and 157,783 m Jl. Airlangga. The results of the flyover solution analysis showed that the vehicle queue length was 54.09 m Jl. Srivijaya; 201.15 m Jl. Gajah Mada; 76.95 m Jl. Majapahit and 107.71 m Jl. Airlangga